Anatomy of malice [computer viruses]. - Cass, S. (IEEE spectrum)
As in controlling the spread of real diseases, the key to effective defenses against computer viruses is to understand the cause and mechanism of infection, not to focus on the symptoms. A computer virus that erases a user's files may seem very different from one that merely prints out the occasional annoying message, but chances are, they both got into the system in a similar fashion. Malicious software falls, by and large, into three classes: Trojans, viruses, and worms. The way in which these viruses work is explained, as are methods to counteract them